2019
DOI: 10.1097/md.0000000000015133
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound image analysis using deep learning algorithm for the diagnosis of thyroid nodules

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 36 publications
1
56
2
2
Order By: Relevance
“…The risk of bias from the reference standard was considered to be unclear in 2 of the included studies [14,23]. The risk of bias from flow and timing was considered to be high or unclear in 7 of the included studies, and these studies adopted pathological examination, fine needle aspiration, and ultrasound as reference standards for diagnosing benign nodules [19,22,25,27,28,30,31].…”
Section: Methodological Quality Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of bias from the reference standard was considered to be unclear in 2 of the included studies [14,23]. The risk of bias from flow and timing was considered to be high or unclear in 7 of the included studies, and these studies adopted pathological examination, fine needle aspiration, and ultrasound as reference standards for diagnosing benign nodules [19,22,25,27,28,30,31].…”
Section: Methodological Quality Of the Included Studiesmentioning
confidence: 99%
“…The flow diagram of the literature search is shown in Figure 1. Nineteen studies with 4,781 nodules used in external validation sets were included in the study, including 6 studies on classic machine learning-based CAD sys-DOI: 10.1159/000504390 tems [14][15][16][17][18][19] and 13 studies on deep learning-based CAD systems [7,[20][21][22][23][24][25][26][27][28][29][30][31]. The general characteristics of the included studies are shown in Table 1, and the detailed characteristics are demonstrated in online supplementary Table 1 (see www.karger.com/doi/10.1159/000504390 for all online suppl.…”
Section: Literature Searches and Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…AI has also been successfully applied to thyroid ultrasound. In a study by Song et al, 1358 thyroid nodule US images were used to train a DL algorithm . The objective of the study was to determine if AI could differentiate malignant from benign thyroid nodules, thus reducing the number of thyroid biopsies performed.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…This kind of system uses and processes one or more captured medical images of some organs such as X-ray, CT, and MRI scans, and yields its decision that can assist doctors in diagnosing diseases. Due to its purpose, CAD systems have been widely developed and used in real-life applications such as for diagnosing the brain [2,3,7,12], breasts [4,8,[13][14][15][16], lungs [10], and thyroid diseases [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%